Flock structure and pair bonds of the Australian Wood Duck Chenonetta jubata - Kingsford, R T (Wildfowl, 1990)
Flocks of Australian Wood Ducks were composed of pairs of birds which moved independently between flocks over periods of more than 24 hours. Sixteen groups formed with a similarity greater than 0.75, following Single Linkage Clustering analysis using the Jaccard similarity coefficient. All were groups of two ducks, invariably male and female. Records confirmed that most of these were paired birds. Only about 40% of a flock remained the same after a period of 24 hours. This declined to 20% over a two day period. After breeding when the young have fledged, family groups joined other individuals in flocks but it was not known how long these family groups remained together. Pair bonds were long-term with six pairs recorded together for more than one year: two pairs were paired for a minimum of 16 months. Pairs remained together throughout the year but pairs did not usually behave independently of other individuals within a flock. Flocks usually behaved as a unit when grazing or loafing. Individuals remained close together while they grazed, with over 50% of the flock grazing at any instant.